Partial Purification and Characterization of Endoproteinases from Senescing Barley Leaves - Miller, Bruce L. (1981)
Two major endoproteinases were purified from senescing primary barley leaves. The major enzyme (EP(1)) appeared to be a thiol proteinase and accounted for about 85% of the total proteolytic activity measured in vitro. This proteinase was purified 5,800-fold and had a molecular weight of 28,300. It was highly unstable in the absence of dithiothreitol or at a pH greater than 7.5. Leupeptin, at a concentration of 10 micromolar, inhibited this enzyme 100%. A second proteinase (EP(2)) was purified approximately 50-fold and had a molecular weight of 67,000. It was inhibited 20% by 1 millimolar dithiothreitol and 50% by 1 millimolar phenylmethyl sulfonylfluoride. EP(2) contributed about 15% of the total proteolytic activity measured in vitro. Both proteinases hydrolyzed a variety of artificial and protein substrates, and both had pH optima of 5.5 to 5.7 when either azocasein or [(14)C]ribulose-1,5-bisphosphate carboxylase ([(14)C]RuBPCase) was the substrate. The thiol endoproteinase hydrolyzed azocasein linearly but hydrolyzed [(14)C]RuBPCase biphasically. A third endoproteinase (EP(3)), not detected by standard proteolytic assays, was observed when [(14)C]RuBPCase was the substrate.